Penegakan Hukum Terhadap Pelaku Tindak Pidana Pemalsuan dan Pengedaran Uang Palsu (Studi Kasus di Wilayah Hukum Kepolisian Resor (Polres) Badung) - Ni Gusti Putu Pradnya Paramita Putri; Anak Agung Sagung Laksmi Dewi; I Made Minggu Widyantara (Warmadewa Press, 2025)
Counterfeit money crime is one form of crime that is very significant in harming the people involved as economic actors and consumers. The problem raised is Law Enforcement Against Perpetrators of Criminal Counterfeiting and Circulation of Counterfeit Money in the Badung Police Law Area and What are the Factors and Efforts to Overcome the Criminal Act of Counterfeiting Counterfeit Money. This thesis research uses empirical research methods in the field of law with a sociological approach. The result of this research is that people who commit criminal acts of counterfeiting and distributing counterfeit money can be sentenced to imprisonment for 15 years in accordance with Law No.7 of 2011. Factors that cause offenders to commit criminal acts of counterfeiting and distribution of counterfeit money due to internal and external factors. Therefore, the countermeasures are preventive and repressive efforts.